An analytical study of the work environment in industrial companies: Evidence from Arab countries - Osama Wagdi; Said Sayed (Cogent Social Sciences)
This study investigated the features of the work environment in Arab industrial companies. This study was conducted by using a quantitative survey with 108 items that correspond to their views and opinions on their work environment and identify their individual stress and productivity levels based on a combination of four preexisting surveys; “Perceived Stress Scale (PSS)”, “Endicott Work Productivity Scale (EWPS)”, “Work Environment Survey (WES)” and “World Health Organisation—Workplace Health and Productivity Questionnaire (WHO-HPQ)”. A total of 434 responses were received on May 2022 from seven Arab countries (Bahrain, Egypt, Jordan, Kuwait, Oman, Qatar, and Saudi Arabia). The study found a difference in the characteristics of the work environment in Arab industrial companies, where there is a difference in the attitudes of workers in those companies towards “Perceived Stress”, “Work Productivity”, “Work Environment”, and “Workplace Health and productivity” between Arab industrial companies according to the country. The study can explain this result according to the difference in financial and technology resources between manufacturing companies in the Arab Gulf versus Egypt and Jordan. Finally, there are two evidences that can be implemented immediately. A significant percentage of unsatisfied work environments are derived from a lack of relationships between supervisors and subordinates. It is therefore advisable for companies to devise a training programme to achieve a healthy work environment on the other hand.